CaMKK2 is not involved in contraction-stimulated AMPK activation and glucose uptake in skeletal muscle - Florentina Negoita; Alex B. Addinsall; Kristina Hellberg; Conchita Fraguas Bringas; Paul S. Hafen; Tyler J. Sermersheim; Marianne Agerholm; Christopher T.A. Lewis; Danial Ahwazi; Naomi X.Y. Ling; Jeppe K. Larsen; Atul S. Deshmukh; et al. (Elsevier, 2023)
Objective: The AMP-activated protein kinase (AMPK) gets activated in response to energetic stress such as contractions and plays a vital role in regulating various metabolic processes such as insulin-independent glucose uptake in skeletal muscle. The main upstream kinase that activates AMPK through phosphorylation of α-AMPK Thr172 in skeletal muscle is LKB1, however some studies have suggested that Ca2+/calmodulin-dependent protein kinase kinase 2 (CaMKK2) acts as an alternative kinase to activate AMPK. We aimed to establish whether CaMKK2 is involved in activation of AMPK and promotion of glucose uptake following contractions in skeletal muscle. Methods: A recently developed CaMKK2 inhibitor (SGC-CAMKK2-1) alongside a structurally related but inactive compound (SGC-CAMKK2-1N), as well as CaMKK2 knock-out (KO) mice were used. In vitro kinase inhibition selectivity and efficacy assays, as well as cellular inhibition efficacy analyses of CaMKK inhibitors (STO-609 and SGC-CAMKK2-1) were performed. Phosphorylation and activity of AMPK following contractions (ex vivo) in mouse skeletal muscles treated with/without CaMKK inhibitors or isolated from wild-type (WT)/CaMKK2 KO mice were assessed. Camkk2 mRNA in mouse tissues was measured by qPCR. CaMKK2 protein expression was assessed by immunoblotting with or without prior enrichment of calmodulin-binding proteins from skeletal muscle extracts, as well as by mass spectrometry-based proteomics of mouse skeletal muscle and C2C12 myotubes. Results: STO-609 and SGC-CAMKK2-1 were equally potent and effective in inhibiting CaMKK2 in cell-free and cell-based assays, but SGC-CAMKK2-1 was much more selective. Contraction-stimulated phosphorylation and activation of AMPK were not affected with CaMKK inhibitors or in CaMKK2 null muscles. Contraction-stimulated glucose uptake was comparable between WT and CaMKK2 KO muscle. Both CaMKK inhibitors (STO-609 and SGC-CAMKK2-1) and the inactive compound (SGC-CAMKK2-1N) significantly inhibited contraction-stimulated glucose uptake. SGC-CAMKK2-1 also inhibited glucose uptake induced by a pharmacological AMPK activator or insulin. Relatively low levels of Camkk2 mRNA were detected in mouse skeletal muscle, but neither CaMKK2 protein nor its derived peptides were detectable in mouse skeletal muscle tissue. Conclusions: We demonstrate that pharmacological inhibition or genetic loss of CaMKK2 does not affect contraction-stimulated AMPK phosphorylation and activation, as well as glucose uptake in skeletal muscle. Previously observed inhibitory effect of STO-609 on AMPK activity and glucose uptake is likely due to off-target effects. CaMKK2 protein is either absent from adult murine skeletal muscle or below the detection limit of currently available methods.